TROUBLING CONSTRUCTS - Duncan, Norman (PINS-Psychology in Society, 2025)
Durrheim, Kevin, Mtose, Xoliswa and Brown, Lyndsay (2011) Race trouble: Race, identity and inequality in post-apartheid South Africa. Pitermaritzburg: UKZN Press. ISBN 978-1-86914-199-8. Pages ix + 234. When I first started reading this book by Durrheim, Mtose and Brown the media was replete with reports on the manifestly racist utterances of the South African author Annelie Botes, and the columnist Kuli Roberts. More recently, an altercation between a white man and a black woman at a gym in Johannesburg reportedly resulted in a barrage of the vilest racist invective directed at the woman (Makhanya, 2012). This incident was also widely covered in the media.